2013
DOI: 10.1007/s00262-013-1391-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of p38 MAPK signaling enhances dendritic cell activation of human CD4+ Th17 responses to ovarian tumor antigen

Abstract: The recent finding that Th17 infiltration of ovarian tumors positively predicts patient outcomes suggests that Th17 responses play a protective role in ovarian tumor immunity. This observation has led to the question of whether Th17 cells could be induced or expanded to therapeutic advantage by tumor vaccination. In this study, we show that treatment of ovarian tumor antigen-loaded, cytokine-matured human dendritic cells (DC) with a combination of IL-15 and a p38 MAP kinase inhibitor offers potent synergy in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 50 publications
1
27
1
3
Order By: Relevance
“…Several mechanisms of tumor-mediated immunesuppression have been identified, including Treg infiltration, expression of B7-H1 and B7-H4 coinhibitory molecules by tumor cells and tumor-associated antigen-presenting cells [26]. Here, we focus on the role of CD8 + Treg in tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Several mechanisms of tumor-mediated immunesuppression have been identified, including Treg infiltration, expression of B7-H1 and B7-H4 coinhibitory molecules by tumor cells and tumor-associated antigen-presenting cells [26]. Here, we focus on the role of CD8 + Treg in tumor immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of the p38 MAP kinase pathway reduce transcription of PD-L1 by DC and may thereby enhance DC-based cancer vaccines [43]. However, these drugs cannot be used in vivo, so other therapy strategies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Epstein-Barr virus-transformed LCL were established from peripheral blood leukocytes (PBL) by infection with the B95.8 strain of Epstein-Barr virus, as described 9 .…”
Section: Methodsmentioning
confidence: 99%
“…In sharp contrast, ovarian tumor expression of IL-17 (produced by infiltrating Th17 T cells) correlates with markedly prolonged overall survival among ovarian cancer patients 6 , leading to the question of whether Th17 cells could be induced or expanded to therapeutic advantage 7,8 . Recent studies have shown that treatment of ovarian tumor antigen-loaded, cytokine-matured dendritic cells (DC) with IL-15 and a p38 MAPK inhibitor (designated DC IL-15/p38inhib ) enhances ERK phosphorylation and biases human CD4 + T cell responses toward a Th1/Th17 phenotype that correlates with strong CD8 + CTL activation 9 .…”
Section: Introductionmentioning
confidence: 99%